The 29.5 kb APOBEC3B Deletion Polymorphism Is Not Associated with Clinical Outcome of Breast Cancer - Liu, Jingjing (PLoS One, 2016)
Increased APOBEC3B mRNA levels are associated with a hypermutator phenotype and poor prognosis in ER-positive breast cancer patients. In addition, a 29.5 kb deletion polymorphism of APOBEC3B, resulting in an APOBEC3A-B hybrid transcript, has been associated with an increased breast cancer risk and the hypermutator phenotype. Here we evaluated whether the APOBEC3B deletion polymorphism also associates with clinical outcome of breast cancer. Copy number analysis was performed by quantitative PCR (qPCR) in primary tumors of 1,756 Dutch breast cancer patients. The APOBEC3B deletion was found in 187 patients of whom 16 carried a two-copy deletion and 171 carried a one-copy deletion. The prognostic value of the APOBEC3B deletion for the natural course of the disease was evaluated among 1,076 lymph-node negative (LNN) patients who did not receive adjuvant systemic treatment. No association was found between APOBEC3B copy number values and the length of metastasis-free survival (MFS; hazard ratio (HR) = 1.00, 95% confidence interval (CI) = 0.90–1.11, P = 0.96). Subgroup analysis by ER status also did not reveal an association between APOBEC3B copy number values and the length of MFS. The predictive value of the APOBEC3B deletion was assessed among 329 ER-positive breast cancer patients who received tamoxifen as the first-line therapy for recurrent disease and 226 breast cancer patients who received first-line chemotherapy for recurrent disease. No association between APOBEC3B copy number values and the overall response rate (ORR) to either tamoxifen (odds ratio (OR) = 0.88, 95% CI = 0.69–1.13, P = 0.31) or chemotherapy (OR = 0.97, 95% CI = 0.71–1.33, P = 0.87) was found. Thus, in contrast to APOBEC3B mRNA levels, the APOBEC3B deletion polymorphism has neither a prognostic nor a predictive value for breast cancer patients. Although a correlation exists between APOBEC3B copy number and mRNA expression, it is relatively weak. This suggests that other mechanisms exist that may affect and therefore determine the prognostic value of APOBEC3B mRNA levels.